Acetylene black interlayer regulated sulfur deposition for lithium-sulfur batteries with high utilization and long-term life. (1st November 2022) - Men, Xin-Liang; Deng, Teng; Jiao, Xue-Chao; Qu, Lai-Tao; Wen, Kai-Ning; Che, Jiang-Xuan; Chen, Li-Ping; Li, Sen; Wang, Juan
Abstract: Lithium-sulfur (Li-S) batteries are considered to be competitive next-generation energy storage systems. However, practical applications are limited due to the shuttle of lithium polysulfides (LiPSs) and the poor electronic conductivity of the sulfur cathode, especially at high-rate currents. Here, we applied commercialized Acetylene black (AB) as separator coating in Li-S batteries. The stacking of AB nanospheres forms a void space that can physically adsorb polysulfides, store electrolytes, and promote lithium-ion diffusion; Simultaneously, it forms an excellent electronic conduction network that significantly improves the utilization of higher-order LiPSs. The thickness and composition of the coating can regulate the nucleation of crystalline S and Li2 S to promote the uniform deposition of solid-phase particles. AB-150 releases an initial capacity of 961.3 mAh g −1 and still maintains at 825 mAh g −1 after 100 cycles with a capacity retention rate of 85.8% at 0.2C. Even remains at 371.2 mAh g −1 after 1000 cycles at 1C with a weak capacity decay rate of 0.06% per cycle. These understandings can also be extended to the design of polar/catalytic interlayer materials driving the large-scale application of Li-S batteries.